Pengaruh Corporate Governance terhadap Integritas Laporan Keuangan - Yandita, Dillanof; Nelvirita, Nelvirita (Universitas Negeri Padang, 2025)
This study investigates the impact of corporate governance factors specifically independent commissioners, audit committees, and internal audits on the integrity of financial reporting in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Employing a multiple linear regression analysis through SPSS and a purposive sampling method, the research selected 20 companies from a total population of 28. The findings reveal that independent commissioners have a detrimental effect on the credibility of financial statements, while audit committees similarly undermine reporting integrity. Additionally, internal audits do not enhance the credibility of financial statements. These results highlight significant weaknesses in corporate governance practices within the industry, underscoring the need for further examination and improvement of governance structures to ensure reliable financial reporting.